Characterization of metal mining wastes and their possible use in engineered barriers - Huillcañahui T., Ramiro (2007)
Experiments of laboratory of characterization of residues of the extractive industry to evaluate the possibility of re-utilization of these (RMM) and calcareous residues come true in this work at the construction of barriers of engineering considering for it the executive I mark 1999/31 CE, on storage of residues (residues mining metallurgic). For the realization of this plan, we did that with the industry of metal trush of Zn and Pb, and metal trush of marmol also for the neutralization. Metallic industry’s residues, fi nd aggregates in The Mining saw of Cartagena -The Union/ Spain. At this zone exist a mining total of 89 rafts of residues metallurgic, many of them containing muds of fl oating, of these have obtained 13 representative signs of residues of fl oating of the different kinds of residues. The residues according to your classifi cation by size of particles classify like slime. The saturated hydraulic permeability is variable with ranges between 10-7 and 10-9 m/s.